1991
DOI: 10.1002/bit.260370208
|View full text |Cite
|
Sign up to set email alerts
|

NADH fluorescence and oxygen uptake responses of hybridoma cultures to substrate pulse and step changes

Abstract: A fiber-optic probe was interfaced to an analytical spectrofluorophotometeru and used to measure NAD(P)H fluorescence of hybridoma cells in a bioreactor. NAD(P)H fluorescence was found to qualitatively represent metabolic state during various induced metabolic transitions. NAD(P)H fluorescence increased immediately following aerobic-anaerobic transitions, and decreased immediately upon transition back to aerobic metabolism. Pulsing of glucose to glucose-depleted cultures caused NAD(P)H fluorescence to first in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…In addition, in group 3 we observed low production of ammonia (8 nmoles/(h 10 6 cells)) and low average ammonia levels (1.2 × 10 −2 g/L) implying low glutamine utilization via aerobic metabolism, which is consistent with previous studies of chick chondrocytes (Rajpurohit et al, 1996) and mouse hybridoma cells (Miller et al, 1987;Siano and Mutharasan, 1991). It was suggested that low oxygen concentrations inhibit the TCA cycle resulting in ␣-ketoglutarate accumulation and low NH 3 production (Miller et al, 1987;Rajpurohit et al, 1996;Siano and Mutharasan, 1991). The cells in constructs from group 3 thus behaved as if under hypoxic conditions even though the measured bulk phase oxygen tension was 43 mmHg.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, in group 3 we observed low production of ammonia (8 nmoles/(h 10 6 cells)) and low average ammonia levels (1.2 × 10 −2 g/L) implying low glutamine utilization via aerobic metabolism, which is consistent with previous studies of chick chondrocytes (Rajpurohit et al, 1996) and mouse hybridoma cells (Miller et al, 1987;Siano and Mutharasan, 1991). It was suggested that low oxygen concentrations inhibit the TCA cycle resulting in ␣-ketoglutarate accumulation and low NH 3 production (Miller et al, 1987;Rajpurohit et al, 1996;Siano and Mutharasan, 1991). The cells in constructs from group 3 thus behaved as if under hypoxic conditions even though the measured bulk phase oxygen tension was 43 mmHg.…”
Section: Discussionsupporting
confidence: 92%
“…Values of Y L/G higher than 2 (2.1-2.2) were also reported by Siano and Mutharasan (1991) in mouse hybridoma cells cultured under hypoxic conditions and attributed to the conversion of glutamine to lactate. In addition, in group 3 we observed low production of ammonia (8 nmoles/(h 10 6 cells)) and low average ammonia levels (1.2 × 10 −2 g/L) implying low glutamine utilization via aerobic metabolism, which is consistent with previous studies of chick chondrocytes (Rajpurohit et al, 1996) and mouse hybridoma cells (Miller et al, 1987;Siano and Mutharasan, 1991).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Metabolic activity can not be measured directly. Respiration and energy conversion can be monitored by oxygen mass balance [13,27] or spectroscopic analysis of NAD/ NADH + H + respectively [41]. A strategy ®rst described by Zhou et al [44] determines the physiological state of the cells on-line during cultivation by the oxygen uptake rate OUR.…”
Section: Introductionmentioning
confidence: 99%
“…Duysens and Amesz first reported the use of on-line fluorescence measurement technique in suspensions of baker's yeast and alga [15]. Thereafter it has been used by several researchers for in situ characterization of biomass and cellular metabolic state using different fermentation processes [13,[16][17][18][19]. The correlation between culture fluorescence and biomass concentration could be made on a reasonable assumption that during the balanced growth of the microorganism the intracellular concentration of NADH+H + remains constant.…”
mentioning
confidence: 98%